Recent advances in treatment and diagnosis of rheumatoid arthritis. Issue 4 (19th February 2014) - Waters, Lisa; Moots, Robert
Abstract Rheumatoid arthritis is a chronic autoimmune condition associated with significant co‐morbidities. Our Drug review discusses the importance of early detection and highlights recent developments in diagnosis and treatment, followed by sources of further information.